2017
DOI: 10.1021/acsami.7b11779
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Ag/Ni Metal-Mesh with Low Surface Roughness As Transparent Conductive Electrode for Optoelectronic Applications

Abstract: Metal-mesh is one of the contenders to replace indium tin oxide (ITO) as transparent conductive electrodes (TCEs) for optoelectronic applications. However, considerable surface roughness accompanying metal-mesh type of transparent electrodes has been the root cause of electrical short-circuiting for optoelectronic devices, such as organic light-emitting diode (OLED) and organic photovoltaic (OPV). In this work, a novel approach to making metal-mesh TCE has been proposed that is based on hybrid printing of silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 38 publications
0
58
0
Order By: Relevance
“…Chen et al [78] reported on fabricated Ag/Ni metal mesh electrodes for QDLEDs using hybrid printing. They polished back the electroplated Ni layer to achieve an extremely smooth surface of embedded metal mesh.…”
Section: Metal Grid Tce-based Qdledsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [78] reported on fabricated Ag/Ni metal mesh electrodes for QDLEDs using hybrid printing. They polished back the electroplated Ni layer to achieve an extremely smooth surface of embedded metal mesh.…”
Section: Metal Grid Tce-based Qdledsmentioning
confidence: 99%
“…To solve this problems, several alternatives such amorphous oxide electrodes, metal grid (mesh), metal nanowire, metal network, carbon nanotube (CNT), graphene, graphene oxide, conducting polymer, and hybrid electrodes have been extensively reported. [10][11][12][13][14][15][16][17][18] In fabricating QDLEDs, several new TCE materials have been employed as anodes or cathodes for hole/ electron injection. With this review, we report on recent research developments in TCEs for QDLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] This is a functional film that is electrically conductive while transmitting light in the visible region. [1,2] This is a functional film that is electrically conductive while transmitting light in the visible region.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Moreover, the thicker metal lines by multiple printing passes would further increase the printed line width, which is challenging to achieve high aspect ratio. [26][27][28] Ag metal-meshes with less than 1 Ω □ −1 sheet resistance and 88% transmittance have been fabricated previously by embedding Ag nanoparticles (NPs) into the roll-to-roll imprinted grooves with 1:1 of depth to width aspect ratio and have been successfully applied to touch panel. [26][27][28] Ag metal-meshes with less than 1 Ω □ −1 sheet resistance and 88% transmittance have been fabricated previously by embedding Ag nanoparticles (NPs) into the roll-to-roll imprinted grooves with 1:1 of depth to width aspect ratio and have been successfully applied to touch panel.…”
mentioning
confidence: 99%
“…[26][27][28] Ag metal-meshes with less than 1 Ω □ −1 sheet resistance and 88% transmittance have been fabricated previously by embedding Ag nanoparticles (NPs) into the roll-to-roll imprinted grooves with 1:1 of depth to width aspect ratio and have been successfully applied to touch panel. [26] Though electroplating can fill up the grooves, Ni is not the best conductive material. [26] Though electroplating can fill up the grooves, Ni is not the best conductive material.…”
mentioning
confidence: 99%